Threads of Heritage: A Comparative Analysis of Nias Batik/Nokanibira and Garot Hanbok Preservation in the Globalization Era - Darynaufal Mulyaman; Bobyano Dolyamano Blessing Purba (Fakultas Teknik Universitas Pekalongan bekerjasama dengan Asosiasi Perajin dan Pengusaha Batik (APPBI), 2026)
Globalization has created significant pressures on the preservation of traditional textile heritage in Indonesia and South Korea. This study examines the preservation strategies of Nokanibira (Nias batik worn in Hombo Batu traditions) and Garot (persimmon-dyed Jeju specialized hanbok), two textile heritages representing local cultural identity amid modernization currents. Using a qualitative approach with the Most Similar System Design (MSSD) comparative method, this research analyzes fundamental differences in preservation approaches between these two textile traditions. Findings reveal that Nokanibira persists through community-based efforts with limited institutional support, while Garot benefits from structured state policies, infrastructure investment, and integration into Jeju's regional development strategies. Although both traditions face similar challenges from global cultural homogenization, differences in institutionalization levels, state roles, and creative economy strategies result in varying degrees of preservation success. This research provides important insights into how comprehensive cultural policies can strengthen the resilience of traditional textile heritage in the globalization era.